2001
DOI: 10.1515/jpm.2001.007
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection and the risk of perinatal mortality in Hungary

Abstract: Nyári et al, Chlamydia trachomatis infection and the risk of perinatal mortality 55 J. Perinat. Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Although the patients tested positive for C. trachomatis may not always have been associated with obvious symptoms, it has major role in perinatal mortality. [20] Control programs emphasizing targeted screening, early diagnosis, and effective treatment will have led to an eventual decline in the incidence of perinatal and neonatal chlamydial infections. [21] Approaches to prevention and treatment of chlamydial infections in pregnant women and infants seem to be necessary, including new antimicrobial interventions and the development of a vaccine strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patients tested positive for C. trachomatis may not always have been associated with obvious symptoms, it has major role in perinatal mortality. [20] Control programs emphasizing targeted screening, early diagnosis, and effective treatment will have led to an eventual decline in the incidence of perinatal and neonatal chlamydial infections. [21] Approaches to prevention and treatment of chlamydial infections in pregnant women and infants seem to be necessary, including new antimicrobial interventions and the development of a vaccine strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended to test pregnant women in the fi rst trimester of gestation (15). Evidence was provided as to the correlation between C. trachomatis infection and premature uterine activity with subsequent signifi cantly higher perinatal mortality in pregnant women positive for C. trachomatis (16,17,18). Effectiveness of screening for C. trachomatis depends to a considerable degree on the diagnostic method used.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports on the risk factors for these infections in the pregnant status. The risk factors for C. trachomatis infection in pregnant women were reported to be young age, unmarried status, history of gonorrhea and first intercourse at less than 17 years of age 14,15 . Also, it was reported that the risk factors for BV were single marital status and high levels of chronic stress during pregnancy 16,17 …”
Section: Introductionmentioning
confidence: 99%